2015
DOI: 10.5137/1019-5149.jtn.15936-15.0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term clinical and electrophysiological outcomes of local steroid injection and surgical decompression in the treatment of carpal tunnel syndrome running title: steroid injection and surgical decompression in carpal tunnel syndrome

Abstract: ABSTRACTand prolonged mechanical pressure causes changes in the myelin sheath (28). Changes in intraneural microcirculation, impairment of axonal transport and alterations in vascular permeability have been detected. All of these cause edema formation and impairment of signal conduction (26).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In the treatment of severe CTS, steroid injection and surgical decompression achieved favorable improvements in clinical and electrophysiological parameters within the short term without superiority of one treatment over the other (6). Therefore, in patients for whom surgical decompression cannot be applied, local steroid injections can be recommended as a less invasive and a promising treatment alternative.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the treatment of severe CTS, steroid injection and surgical decompression achieved favorable improvements in clinical and electrophysiological parameters within the short term without superiority of one treatment over the other (6). Therefore, in patients for whom surgical decompression cannot be applied, local steroid injections can be recommended as a less invasive and a promising treatment alternative.…”
Section: Variablesmentioning
confidence: 99%
“…According to the Cochrane database, local steroid injection for CTS provides greater clinical improvement in symptoms 1 month after injection compared with placebos (4,5). In our previous study, we found that local steroid injection and surgical decompression achieved favorable improvements in clinical and electrophysiological parameters within the short term without superiority of one treatment over other (6). Therefore, in patients for whom surgical decompression cannot be applied, a local steroid injection can be recommended as a less invasive and promising treatment alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Gurcay et al investigated the effectiveness of LCI and surgery in the treatment of patients with severe CTS. They reported that LCI and surgical decompression achieved significant clinical and electrophysiological improvements within a three-month period without superiority of one treatment over other 36 . The authors recommended that LCI could be applied as a less-invasive treatment alternative in patients with severe CTS.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial by Gurcay Ag and his colleagues shows the equivalent effect of steroid injection and surgical decompression in the improvement of clinical and electrophysiological parameters in a short-term period in patients with severe CTS. They indicated that local steroid injection is a viable option in patients for whom surgical decompression is contraindicated or undesirable [13].…”
Section: Hui Et Al Demonstrated That Open Carpal Tunnel Re-mentioning
confidence: 99%